THE EFFECTIVENESS OF FASTING IN MANAGING SEXUAL DESIRE: A BIBLIOMETRIC ANALYSIS FROM AN ISLAMIC PERSPECTIVE (2015–2024) - Wan Muhayudin, Ahmad Akmal; Talib, Noor Husna; Zulkifli, Muhammad Firdhaus; Abdullah, Mohammad Roshimi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study presents a bibliometric analysis on the topic of the effectiveness of fasting in managing sexual desire, aiming to uncover scholarly trends, key contributors, and research patterns in this niche but increasingly relevant field. The research is motivated by the growing interest in Islamic psycho-spiritual approaches to managing human desires, particularly in response to rising social concerns such as premarital sex and hypersexualized content in digital media. Despite the traditional and spiritual significance of fasting in Islam, little is known about the academic development of this subject from a bibliometric standpoint. The study employed three main keywords: Islamic, fasting, and desires, in order to retrieve data from the Scopus database using advanced title-based search parameters to ensure content relevance. The inclusion criteria focused on English and Arabic language articles published in peer-reviewed journals between 2015 and 2024. The initial dataset was refined using OpenRefine for data cleaning and deduplication, followed by analysis through the Scopus Analyzer and VOSviewer software for mapping co-authorship, keyword co-occurrence, and country collaboration networks. A total of 736 documents were included in the final dataset. The numerical results indicate that the United States, United Kingdom, and Canada are among the most active contributors, while keywords such as "Ramadan," "spirituality," and "self-control" frequently co-occur with fasting-related studies. The visualized networks highlight significant collaborative potential across Islamic and non-Islamic research contexts. In conclusion, the findings demonstrate an emerging scholarly interest in the intersection between Islamic practices and psychological well-being. This study offers valuable insight into how Islamic fasting is conceptualized within academic discourse and identifies gaps and opportunities for future interdisciplinary research, particularly in the domains of Islamic studies, psychology, and health sciences.